Audit Fee Determinants for Mainland Chinese Companies Listed on Hong Kong Stock Exchange - Lou, Jie (2008)
Research in audit service market has grown significantly since the first study published in 1980. The surge of Mainland Chinese companies listing on Hong Kong Stock Exchange and the different characteristics associated with Chinese domestic and Hong Kong audit markets have inspired this work to determine the audit service pricing models of these companies.